Characterizing Pain and Generalized Sensory Sensitivity According to Trauma History Among Patients With Knee Osteoarthritis. Issue 9 (30th December 2020) - Pierce, Jennifer; Hassett, Afton L; Brummett, Chad M; McAfee, Jenna; Sieberg, Christine; Schrepf, Andrew; Harte, Steven E
Abstract: Background: Childhood trauma and adversity have been linked to chronic pain and pain sensitivity, particularly centralized pain. Yet, there remain numerous gaps in our understanding of this link. Purpose: We explored the association between nonviolent and violent childhood trauma and a component of centralized pain (i.e., generalized sensory sensitivity) and pain sensitivity using self-report measures of centralized pain and quantitative sensory testing (QST). Methods: Patients scheduled for a total knee arthroplasty ( n = 129) completed questionnaires and QST prior to surgery. Results: We found that self-report measures of centralized pain (i.e., widespread pain, somatic awareness, and sensory sensitivity) displayed a graded relationship across trauma groups, with patients with a history of violent trauma reporting the highest scores. Univariable multinomial logistic regression analyses showed that higher sensory sensitivity was associated with increased risk of being in the nonviolent trauma group compared to the no trauma group. Furthermore, higher widespread pain, higher somatic awareness, and higher sensory sensitivity distinguished the violent trauma group from the no trauma group. In multivariable analyses, sensory sensitivity is uniquely distinguished between the violent trauma group and the no trauma group. QST did not distinguish between groups. Conclusions: The findings highlight the need for future research and interventions that reduce sensory sensitivity for chronic pain patients with a history of violent childhood trauma. Abstract : Increased sensory sensitivity is linked to higher risk of reporting a history of childhood trauma, especially violent trauma, compared to no trauma in childhood.